Role of Soft Skills in Enhancing Graduate Employability: A Systematic Review from Developing Economies - Paneru, Narendra Raj; Bohara, Bhuban Bahadur; Bishwokarma, Babu Ram (Innovative Research Journal, 2026)
Graduate employability has become a major challenge for universities, employers, and policymakers in developing economies due to rapidly changing workplace needs. In this regard, a persistent mismatch between universities’ graduates’ competencies and employers’ expectations can be clearly observed over the years. This systematic review attempts to synthesize empirical evidence on the role of soft skills in enhancing graduate employability in developing economies. Following the PRISMA 2020 framework, this systematic review analyzed 22 peer-reviewed articles published between 2015 and 2025 through the multistage screening process. This review identifies communication, collaboration, teamwork, critical thinking, complex problem-solving, adaptability, leadership, emotional intelligence, professionalism and life-long learning as the soft skills usually associated with graduate employability. The reviewed studies consistently value these transferable soft skills alongside or often above disciplinary expertise. Despite this fact, universities continue to face challenges in embedding soft skills effectively in their theory-oriented curricula due to which university graduates get limited workplace readiness. Furthermore, evidence from the reviewed studies indicates that experiential learning, work-integrated learning, learner-centered pedagogies, industry-academia collaboration, authentic assessment and curriculum redesign substantively enhance graduate employability. By synthesizing evidences from the Global South, this review identifies the thematic patterns and research gaps on the basis of which evidence-based recommendations are provided to the universities, employers and policy makers regarding the better alignment of graduate competencies with evolving workplace demands.